Strengthening the Value of Pancasila in Elementary Schools in Online Learning Through Whatsapp Group Media - Maulidayani, Tiana; Muktiarni, M; Mupita, Jonah (Universitas Pendidikan Indonesia (UPI), 2022)
Pancasila is a formulation and guideline in the life of the nation and state for the people of all Indonesia. In applying the values in Pancasila, this can be done in various ways such as using a media application called WhatsApp. Material on Pancasila will be given in the group so that students can easily gain knowledge about the values contained in Pancasila.Â